2018
DOI: 10.1371/journal.pone.0198801
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing eating behavior and dietary intake among resident students in a public university in Bangladesh: A qualitative study

Abstract: BackgroundOver the past decades, Bangladesh has made substantial progress in improving higher education, and in part, this was achieved by promoting residence based higher education in public universities. University residency is considered a crucial period for students to develop healthy eating habits and adopt nutritious intake, which comprise a strong foundation for good health throughout life. Although, there is extensive literature on eating behaviors and dietary intake internationally, there appears to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 34 publications
7
97
0
5
Order By: Relevance
“…Mereka melewatkan makan demi mempersiapkan ujian dan mereka hanya mengkonsumsi teh,kopi, dan makanan ringan. 35 Penelitian lain yang dilakukan pada mahasiswa universitas di Jerman menunjukkan bahwa adanya aktivitas akademik mengurangi waktu mereka untuk memasak. 36 Berdasarkan data pada Tabel 2 diperoleh bahwa mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Syiah Kuala yang tidak mengalami GERD (82,4%) lebih banyak dibandingkan dengan mahasiswa yang mengalami GERD (17,6%).…”
Section: Copyright ©2020 P-issn : 2337-6236; E-issn : 2622-884xunclassified
“…Mereka melewatkan makan demi mempersiapkan ujian dan mereka hanya mengkonsumsi teh,kopi, dan makanan ringan. 35 Penelitian lain yang dilakukan pada mahasiswa universitas di Jerman menunjukkan bahwa adanya aktivitas akademik mengurangi waktu mereka untuk memasak. 36 Berdasarkan data pada Tabel 2 diperoleh bahwa mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Syiah Kuala yang tidak mengalami GERD (82,4%) lebih banyak dibandingkan dengan mahasiswa yang mengalami GERD (17,6%).…”
Section: Copyright ©2020 P-issn : 2337-6236; E-issn : 2622-884xunclassified
“…However, another additional factor that is seldom taken into account is that not only is it important to make dietary recommendations on the best composition of the diet to achieve healthy aging but to also study the factors that contribute to their adherence to such recommendations [ 20 , 21 ]. In general, people prefer to eat foods they like [ 21 , 22 , 23 ] and taste is one of the most important factors when making the choices [ 21 , 22 , 24 , 25 ]. Although there is huge inter-individual variation in the perception of the five basic tastes (sweet, salty, bitter, sour and umami) [ 26 , 27 , 28 ], little is known about the influence of such variation on the intake patterns of certain foods [ 29 , 30 ] or even on preferences for certain tastes [ 26 , 27 , 31 , 32 ], emphasizing the need for further research.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies on different populations, it was shown that higher nutrition knowledge was associated with an adoption of healthier lifestyles and food choices [4,5], albeit this association is still controversial or has limited value [6]. Other factors, including social-economic status of the family and traditions, taste preferences, and genetics, are strong drivers that influence individual dietary habits [6][7][8]. Previous research indicated that the food choices of Romanians are largely driven by economic reasons [9].…”
Section: Introductionmentioning
confidence: 99%